1994
DOI: 10.1161/01.hyp.24.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidon-sensitive conversion of big endothelin-1 and degradation of endothelin-1 in rat kidney.

Abstract: We investigated the intrarenal conversion of big endothelin-1 (ET-1) to ET-1 in the isolated perfused rat kidney. Big ET-1 caused a concentration-dependent increase in perfusion pressure, and the pressor molar potency of the pepride was 50-fold less than that of ET-1. The big ET-1 (2xlO" 8 mol/L)-induced pressor action was accompanied by increases in immunoreactive endothelin levels in both the perfusate and renal tissues. Phosphoramidon (10~4 mol/L), a metalloproteinase inhibitor, significantly suppressed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The inability of the chymase inhibitor, chymostatin (Hisaki et al , 1994), to prevent DAG accumulation in response to big ET‐1 in our study, indicates that chymase does not mediate an alternative pathway for big ET‐1 conversion to ET‐1 in the PT. The amount of ET‐1 present in the tissue following exposure to big ET‐1 is thought to be a measure of the functional conversion of big ET‐1 (Hisaki et al , 1994; Fujita et al , 1994). Accordingly, phosphoramidon abolished the accumulation of ET‐1 in lung and renal tissue following perfusion with big ET‐1 (Hisaki et al , 1994; Fujita et al , 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inability of the chymase inhibitor, chymostatin (Hisaki et al , 1994), to prevent DAG accumulation in response to big ET‐1 in our study, indicates that chymase does not mediate an alternative pathway for big ET‐1 conversion to ET‐1 in the PT. The amount of ET‐1 present in the tissue following exposure to big ET‐1 is thought to be a measure of the functional conversion of big ET‐1 (Hisaki et al , 1994; Fujita et al , 1994). Accordingly, phosphoramidon abolished the accumulation of ET‐1 in lung and renal tissue following perfusion with big ET‐1 (Hisaki et al , 1994; Fujita et al , 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of ET‐1 present in the tissue following exposure to big ET‐1 is thought to be a measure of the functional conversion of big ET‐1 (Hisaki et al , 1994; Fujita et al , 1994). Accordingly, phosphoramidon abolished the accumulation of ET‐1 in lung and renal tissue following perfusion with big ET‐1 (Hisaki et al , 1994; Fujita et al , 1994). In the present study, inhibition of ECE was demonstrated by the reduction of tissue ET‐1 content, in cortical slices pretreated with phosphoramidon and incubated subsequently with big ET‐1, to the level observed in slices not exposed to big ET‐1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Phosphoramidon is not entirely specific for NEP because, at high concentrations, it may also inhibit endothelin-converting enzyme. 18 Therefore we tested the effect of the specific NEP inhibitor SCH 39370 17 on the formation of BK- (1-7). The results were very similar to those obtained with phosphoramidon.…”
Section: Inhibition Of Kallidin and Bradykinin Degradation By Enzyme mentioning
confidence: 99%
“…14,15 It follows that ET activity might be modified by local synthesis and/or degradation. Indeed, many tissues have both the synthetic and degradation machinery for ET-1 including kidneys, 16 suggesting local production and degradation of ET-1 that modulates tissue function in an autocrine/paracrine manner (see below).…”
Section: Overview Of Et Biologymentioning
confidence: 99%